Objective Evaluation of Skill Acquisition in Novice Microsurgeons - Brosious, John P.; Tsuda, Shawn T.; Menezes, John M.; Baynosa, Richard C.; Stephenson, Linda L.; Mohsin, Adnan G.; Wang, Wei Z.; Zamboni, William A. (Journal of Reconstructive Microsurgery, 2012)
Introduction Medical training is increasingly focused on patient safety, limiting the ability to practice technical skills in the operative arena. Alternative methods of training residents must be designed and implemented.Methods Three expert microsurgeons were solicited to develop two drills to help residents acquire the basic subset of skills in microsurgery. The first drill was performance of five consecutive simple interrupted sutures on a rubber glove. Expert proficiency was considered a drill time of two standard deviations from expert mean. The drill was performed up to 10 times until completion of the task at expert proficiency. The second drill was performance of an anastomosis on silastic tubing. Residents performed the drill sequentially until performing two consecutive drills at expert proficiency.Results Eight residents with no microsurgical experience volunteered. Six of the eight residents were able to perform the rubber glove drill at expert proficiency within 10 attempts, with an average of 5.3. All of the residents were able to perform two consecutive silastic tubing drills at expert proficiency within nine attempts, with an average of 5.4.Conclusion Residents were able to acquire a basic subset of microsurgical skills within a reasonable time period using these drills.
Keywords: microsurgery; skill training method; anastomosis